Humic matter and phytoplankton nutrient limitation in a changing environment - Wentzky, Valerie (2015)
Climate change leads to increased inputs of terrestrial dissolved organic carbon (DOC) and associated nutrients to freshwaters, potentially affecting the risk for eutrophication. While the effect of higher DOC concentrations on primary productivity (PP) due to light attenuation and increased competition by bacteria is rather well studied, the effect of DOC on PP due to effects on nutrient availability is still unclear. Therefore, laboratory incubation experiments with natural phytoplankton communities were performed to investigate the effect of DOC on phytoplankton growth under different phosphorus (P) and iron (Fe) regimes, under exclusion of light and grazing effects. The experiments were conducted with water originating from two sites with differing DOC character within Lake Mälaren, the third largest lake in Sweden. P (ambient, 50 μg L-1 added), Fe (ambient, 400 μg L-1 added) and DOC (low, ambient, high) concentrations were crossed in all possible combinations giving 12 different treatments. Chlorophyll a concentrations and initial and final chemical conditions were analysed after 7.5 days of incubation.